2007
DOI: 10.1021/jf061440y
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue Analysis of Seven Anticoagulant Rodenticides by High-Performance Liquid Chromatography/Electrospray/Mass Spectrometry

Abstract: Mice and rat populations are commonly controlled by two classes of rodenticide anticoagulants, coumarins and indandiones. However, poisoning of nontarget animals also often occurs. For cases such as these, a rapid, multiresidue method, which provides positive confirmation for both classes of anticoagulant rodenticides, is needed by diagnostic laboratories. A method was developed for the determination of seven anticoagulant rodenticides, coumafuryl, pindone, warfarin, diphacinone, chlorophacinone, bromadiolone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…A developed LC-MS ⁄ MS method should provide confirmation of multiple analytes but should also be sufficiently sensitive to allow identification at trace concentrations in the desired matrices. Recently, LC-ESI-MS has been used for the simultaneous determination of frequently used coumarin and indandione anticoagulant rodenticides in matrices like animal feed stockages, beverages (Marek & Koskinen, 2007) and whole blood (Jin & Chen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A developed LC-MS ⁄ MS method should provide confirmation of multiple analytes but should also be sufficiently sensitive to allow identification at trace concentrations in the desired matrices. Recently, LC-ESI-MS has been used for the simultaneous determination of frequently used coumarin and indandione anticoagulant rodenticides in matrices like animal feed stockages, beverages (Marek & Koskinen, 2007) and whole blood (Jin & Chen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Jin and Chen [16] described the rapid determination of the three anticoagulant rodenticides bromadiolone, flocoumafen and brodifacoum in whole blood by LC-ESI-MS. HLPC-MS/MS assays were developed for the determination of flocoumafen and brodifacoum [17], coumatetralyl [18] and bromadiolone [19], at trace levels in whole blood which can be of use in the diagnosis of poisoned human beings. Marek and Koskinen [20] on the other hand described LC-ESI-MS/MS as a method to confirm and quantify seven anticoagulant rodenticides in diverse matrices such as animal feed stocks, baits and liquid matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the detection and quantitation of the anticoagulant rodenticides in biological matrices, such as blood and liver, may not be comparable between studies. There is considerable variation in the techniques used to recover rodenticides from sample matrices, as well as in the chemical analysis methods used to detect them (Goldade et al 1998, Marek and Koskinen 2007, Vandenbroucke et al 2008, Thomas et al 2011. One study found that the chemical analysis method could significantly underestimate the prevalence of SGARs in wildlife (Dowding et al 2010).…”
Section: Effects Of Anticoagulant Rodenticide Exposurementioning
confidence: 99%